Application of Artificial Intelligence System in Libraries through Data Mining and Content Filtering Methods. Issue 4 (June 2021) - Tian, Zhaoxia
Abstract: With the rapid advancement of artificial intelligence theory, this paper adopts a multi-intelligent agent collaboration method and derives through data mining. In combination with content filtering methods and intelligent agent learning optimization, it improves the high performance by using a personalized information service system architecture. The performance of the library system of vocational colleges. According to the difference of readers' interest, it matches the results of traditional document retrieval, effectively filtering out readers' demand information, reducing the time for readers to search for required information, improving reader retrieval efficiency, realizing information push of similar users, and realizing "information looking for people".